2013
DOI: 10.1590/s1806-83242013000600011
|View full text |Cite
|
Sign up to set email alerts
|

Classification of bifid mandibular canals using cone beam computed tomography

Abstract: The objective of this study was to classify the morphology of bifid mandibular canals and to evaluate their relationship with the roots of third molars, using cone beam computed tomography (CBCT) scans. The CBCT scans of 75 patients were analyzed and the bifurcations were classified according to Langlais et al. (1985). The relationship of bifurcation and third molars was established according to the following classification: class A -uninvolved, class B -close relationship, class C -intimate relationship and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 26 publications
2
24
0
4
Order By: Relevance
“…CBCT scans provide clearer images of the mandibular canal when compared to digital panoramic radiographs as they are free of overlap and other problems inherent to panoramic radiographs. [3] In the present study, CBCT images of 23 patients demonstrated bifid mandibular canal out of 408 CBCT images accounting for the prevalence of 5.63%. Males were found to be predominant over females for the presence of bifid mandibular canal.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…CBCT scans provide clearer images of the mandibular canal when compared to digital panoramic radiographs as they are free of overlap and other problems inherent to panoramic radiographs. [3] In the present study, CBCT images of 23 patients demonstrated bifid mandibular canal out of 408 CBCT images accounting for the prevalence of 5.63%. Males were found to be predominant over females for the presence of bifid mandibular canal.…”
Section: Discussionmentioning
confidence: 49%
“…Correr et al, in 2013, [3] found majority of bifurcations to be Type 1U showing Class C, i.e., intimate relationship with the roots of the third molar. However, in the present study, Type 2BC was the most common bifurcation seen followed by Type 1U, 1B, 2UR, 2UC, and Type 4 canal.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations